One-pot synthesis of hexagonal mesoporous silica confined Ni based catalysts with advanced CO2 methanation performance. (1st February 2023) - Xu, Leilei; Xu, Chunying; Chen, Bin; Bian, Yufang; Wen, Xueying; Cheng, Ge; Wu, Cai-e; Qiu, Jian; Chen, Mindong
Graphical abstract: Highlights: ▶ The Ni-HMS catalyst was facilely synthesized by one-pot method at room temperature. ▶ The Ni active sites were highly dispersed among the mesoporous HMS frameworks. ▶ The in-situ DRIFTS and online TPSR of CO2 methanation revealed reaction pathways. ▶ The anchor effect of Ni active sites improved the anti-sintering performance. ▶ The Ni-HMS performed higher CO2 methanation activity than supported Ni catalysts. Abstract: In this work, a series of hexagonal mesoporous silica (HMS) confined Ni-based CO2 methanation catalysts were successfully synthesized by the facile one-pot strategy. In the Ni-HMS system, the metallic Ni active sites were embedded in the framework of HMS support. Hence, the metallic Ni active sites were highly dispersed and stably confined by the HMS framework. The kinetic study demonstrated that the Ni-HMS catalysts behaved much lower apparent activation energy than the 15Ni/HMS and 15Ni/SiO2 catalysts, accounting for their enhanced low-temperature activities. Meanwhile, the online TPSR and in-situ DRIFTS of the CO2 methanation were employed to study the reaction intermediates over these catalysts. The CHOO–, CH x O-, and CO x were considered as the reaction intermediates over the Ni-HMS catalysts and the possible reaction pathways were also proposed. In conclusion, the Ni-HMS catalysts were considered as a series of efficient and stable catalyst candidates for CO2 methanation.